Emission of Mortgage Bonds on the Example of Polish and British Market - Lechowicz, Tomasz (Journal of Finance and Financial Law, 2015)
Mortgage bond is a form of real estate financing based on assets. Not all types of assets can be used as collateral for mortgage bonds. They must comply with very strict criteria in order to achieve the objectives of the initiator was not threatened. One of the goals is to raise capital to conduct further operations and development.